1996
DOI: 10.1523/jneurosci.16-24-07981.1996
|View full text |Cite
|
Sign up to set email alerts
|

Origin of Oligodendrocytes within the Human Spinal Cord

Abstract: To determine the time and site of origin of the oligodendrocyte lineage in the developing human spinal cord, we have examined tissues from 45 to 83 d postconception (dpc) using sets of probes and antibodies recognizing oligodendrocyte-specific glycolipids, transcripts, and proteins. We found that two clusters of oligodendrocyte precursors appear on or before 45 dpc on each side of the cord ventral ependyma above the floor plate. These precursors express glycolipids recognized by the O4 and Rmab antibodies, pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 64 publications
6
49
1
Order By: Relevance
“…Despite the morphological diversity of human pre-OLs, their immunohistochemical phenotype identified them as oligodendroglial in origin and distinct from astroglia, resting or reactive microglia, and neuronal precursors. Restricted foci of O4-positive progenitors were detected in the ventral ventricular zone of the human spinal cord as early as 6 weeks (Hajihosseini et al, 1996). In agreement with most (Levine et al, 1993;Nishiyama et al, 1997;Reynolds and Hardy, 1997;Chang et al, 2000) but not all (Pouly et al, 1999) studies, our results in developing human brain also indicate that NG2 is specific to the OL lineage in vivo.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Despite the morphological diversity of human pre-OLs, their immunohistochemical phenotype identified them as oligodendroglial in origin and distinct from astroglia, resting or reactive microglia, and neuronal precursors. Restricted foci of O4-positive progenitors were detected in the ventral ventricular zone of the human spinal cord as early as 6 weeks (Hajihosseini et al, 1996). In agreement with most (Levine et al, 1993;Nishiyama et al, 1997;Reynolds and Hardy, 1997;Chang et al, 2000) but not all (Pouly et al, 1999) studies, our results in developing human brain also indicate that NG2 is specific to the OL lineage in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…We also did not observe migratory streams of OL progenitors, but rather pre-OLs were diffusely distributed throughout the white matter by 18 weeks. In contrast to the rodent spinal cord (for review, see Hardy, 1997), in which the migration of OL progenitors occurs at midgestation, O4ϩ progenitors migrate from the human ventral ventricular zone of the cord considerably earlier between 6 and 8 weeks (Hajihosseini et al, 1996). NG2ϩ OL progenitors are abundant in the adult rat and human brain (Levine et al, 1993;Nishiyama et al, 1996Nishiyama et al, , 1997Reynolds and Hardy, 1997;Ong and Levine, 1999;Chang et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the 12q13-15+ GBMs, the EGFR-overexpressing GBMs expressed elevated levels of cyclin D2 (two fold increase, P ¼ 0.03; Table 1). The 12q13-15-upregulated GBMs were also significant for high levels of transcription of oligodendroglial genes (MBP, MAG, PLP1, Nkx2.2, Mal and Sox10) (Hajihosseini et al, 1996;Landry et al, 1997;Zhou et al, 2001;Fu et al, 2002). (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…12q13-15+ tumors were remarkable for upregulation of oligodendroglial genes, including MAG, MBP, PLP1, Nkx2.2, Sox10, Mal and 2 0 ,3 0 -cyclic nucleotide 3 0 , phosphodiesterase-3-CNP (Hajihosseini et al, 1996;Landry et al, 1997;Zhou et al, 2001;Fu et al, 2002). Morphologically, these tumors were GBMs, not oligodendrogliomas or mixed gliomas, and they contained equal level of GFAP transcripts relative to the non-12q13-15+ tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas in adult rodent CNS Nogo-A is localized primarily in oligodendrocytes (Chen et al, 2000), during early development Nogo is associated with neurons. The onset of oligodendrocyte development in the chick and human has been previously determined by O4 immunostaining and occurs around E5-E6 in the chick and around 45 days of gestation in humans, whereas the onset of myelination is observed around E12 in chick and 20 weeks of gestation in humans (Ono et al, 1995;Tanaka et al, 1995;Hajihosseini et al, 1996;Grever et al, 1997). In this study, we have shown that, in the chick spinal cord, both Nogo-A transcript and protein can be detected at E3, a time when motor neurons are being generated and axon outgrowth begins, well before the onset of O4 expression.…”
Section: Nogo Is Developmentally Regulatedmentioning
confidence: 99%